PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PHET TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Ica Nurhikmah; Erna Suwangsing; Wina Mustikaati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of the Problem-Based Learning (PBL) model integrated with PhET interactive simulations on the enhancement of elementary students' mathematical understanding. The persistent issue of students’ low conceptual comprehension in mathematics often stems from teacher-centered instruction and limited student engagement. The research is framed around two primary objectives: (1) to examine the effect of the PBL model supported by PhET media on students’ mathematical understanding, and (2) to compare the improvement in mathematical comprehension between students exposed to the PBL model with PhET and those taught through conventional instructional approaches. This research adopts a quasi-experimental method with a nonequivalent control group design. The participants were fourth-grade students at SDN 2 Sindangkasih, Purwakarta Regency. Data were collected using a mathematical understanding test and analyzed using an independent sample t-test to determine statistical significance. The findings reveal a significant impact of the PBL model assisted by PhET media on students’ mathematical understanding. These results suggest that problem-based instruction, when supported by interactive digital media, can foster deeper and more meaningful mathematical comprehension among elementary learners.